The Clinical Quality Fellowship Program: Developing Clinical Quality Leadership in the Greater New York Region. (March 2018) - Bhalla, Rohit; Jalon, Hillary S.; Ryan, Lorraine
The Institute of Medicine has noted that a key factor underlying patient safety problems in the United States is a paucity of quality and safety training programs for clinicians. The Greater New York Hospital Association and United Hospital Fund created the Clinical Quality Fellowship Program (CQFP) to develop quality improvement leaders in the New York region. The goals of this article are to describe the CQFP's structure and curriculum, program participants' perceived value, improvement projects, and career paths. Eighty-seven participants completed the CQFP from 2010 to 2014. Among program participants completing self-assessment evaluations, significant improvements were observed across all quality improvement skill areas. Capstone project categories included inpatient efficiency, transitional care, and hospital infection. Fifty-six percent of participants obtained promotions following program completion. A training program emphasizing diverse curricular elements, varied learning approaches, and applied improvement projects increased participants' self-perceived skills, generated diverse improvement initiatives, and was associated with career advancement.